2014
DOI: 10.1519/jsc.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Could Biochemical Liver Profile Help to Assess Metabolic Response to Aerobic Effort in Athletes?

Abstract: Monitoring and optimizing the effectiveness of training course require wide analyses of athletes' blood parameter changes. The aim of this study was to evaluate the usefulness of biochemical liver profile to assess the metabolic response to semi-long-distance outdoor run in football players. Sixteen football players run outdoor for 60 minutes to achieve aerobic metabolism. Plasma activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), γ-glutamyltransferase (GGT) and plasma levels of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
14
1
2
Order By: Relevance
“…This study provides further evidence that among former athletes, interpretation of blood aminotransferases activities should consider the release of aminotransferases from skeletal muscle, especially given that no other significant changes in liver clinical parameters (e.g., GGT, bilirubin total and direct, total protein, albumin) during the 4-month-long study were observed. It is also worth noting that in comparison to our previous results [8,35,36], the current findings confirm that changes in AST and ALT activities emerge before any increase in CK activity. LDH activity is often considered a marker of muscle cell damage, as a rise in its concentration is concomitant with disruption to the sarcoma [37][38][39].…”
Section: The Impact Of the Training Program On Biochemical Plasma Prosupporting
confidence: 88%
See 2 more Smart Citations
“…This study provides further evidence that among former athletes, interpretation of blood aminotransferases activities should consider the release of aminotransferases from skeletal muscle, especially given that no other significant changes in liver clinical parameters (e.g., GGT, bilirubin total and direct, total protein, albumin) during the 4-month-long study were observed. It is also worth noting that in comparison to our previous results [8,35,36], the current findings confirm that changes in AST and ALT activities emerge before any increase in CK activity. LDH activity is often considered a marker of muscle cell damage, as a rise in its concentration is concomitant with disruption to the sarcoma [37][38][39].…”
Section: The Impact Of the Training Program On Biochemical Plasma Prosupporting
confidence: 88%
“…The benefits of PA on psychosocial and cognitive health have been also confirmed [2][3][4]. Further, PA has a beneficial effect on general health conditions and induces metabolic changes that are manifested in hematological changes of clinical biochemistry parameters [5][6][7][8]. Health-Related Fitness (H-RF), which is developed during various training programs, is also associated with an improvement of the general well-being.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Os autores analisaram os atletas em diversas fases do período de treinamento e apontaram que especial atenção deve ser dada ao final da fase de preparação e ao final do período competitivo, pois, os parâmetros sanguíneos indicaram que, nestes pontos do tempo, os jogadores estão sob tensão física excessiva e estão sob risco aumentado de apresentar OTS. Em concordância com estes achados, Milanez et al(23), em estudo observacional com seguimento de 5 semanas, encontrou diminuição nos níveis de IgA com o aumento das cargas de trabalho. O autor conclui em seu trabalho que é válida a observação das alterações dos níveis de IgA (salivar) para a prevenção de um possível quadro de OTS.…”
unclassified
“…).Em adição, a elevação das concentrações de CK, LDH, AST e ALT podem ser realizadas como exames complementares, tendo em vista identificar sintomas concernentes à fadiga residual, monitoramento e controle do processo de treinamento, overreaching e, em casos mais severos, o overtraining(LEHMANN;KEUL, 1993;SILVA et al, 2001;CHAMERA et al, 2014). De fato, vale destacar que as mensurações de CK, LDH, AST e ALT substancialmente devem ser realizadas conjuntamente, a fim de não cometer erros de interpretação no diagnóstico dos resultados dos exames, tendo em consideração o dano fim, é considerável frisar que os valores de referência podem se diferenciar mediante a técnica de análise, armazenamento da amostra, preparo do reagente e marca do kit.Portanto, o processamento das análises deve ser efetivado seguindo a padronização preconizada pelo kit do fabricante.No tocante à pesquisa elaborada porRibeiro et al (2006) foram mensuradas as concentrações de AST, ALT, CK e LDH antes e após lutas fragmentadas de 90s, 180s e 300s em 12 atletas experientes de judô.…”
unclassified